Fertilizer type and irrigation frequency affect plant growth, yield, and gas exchange of containerized strawberry cultivars - Geoffrey T. Lalk; Guihong Bi; Eric T. Stafne; Tongyin Li (Technology in Horticulture)
Small-scale strawberry production in southeastern states requires cultivars adaptive to local climates and with season extension potentials. This study investigated plant growth, yield, gas exchange, and fruit quality of ten strawberry (Fragaria × ananassa Duch.) cultivars affected by fertilizer type and irrigation frequency in a containerized production system in 2018. Bare root liners of seven June-bearing and three day-neutral cultivars were grown in 2-gallon containers, fertilized with a conventional fertilizer or an organic fertilizer at comparable rates, and irrigated once or twice daily with the same total irrigation volume. Strawberry cultivars varied in vegetative growth (including plant growth index (PGI), leaf SPAD, number of crowns, visual score, and root dry weight) and fruiting characteristics (including first harvest date, yield, number of fruit, berry size, fruit soluble solids content, and firmness). Day-neutral cultivars 'Evie 2' and ‘Seascape’ produced the highest total yields and late-season yield in June. The conventional fertilizer resulted in higher PGI, leaf SPAD, plant visual score, fruit yield in May, daily water use, and net photosynthetic rate than the organic fertilizer. Two irrigations per day increased substrate moisture compared with one irrigation per day, and increased shoot dry weight with the conventional fertilizer application. Irrigation frequency did not affect PGI, leaf SPAD, gas exchange, fruit yield, or quality in tested strawberry cultivars.